Faith in Flux: Navigating Laypeople’s Post-Secular Religiosity in the Pandemic Era - Muwaffiqillah, Moch.; Kadi, Kadi; Lukman Hakim; Indana Zulfa (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2024)
This study examines the adaptation of religious practices by Muslim communities during the COVID-19 pandemic, navigating the unique challenges of reconciling religious adherence with the imperative to follow scientifically informed health protocols. This research investigates how the general populace integrates Islamic religious practices within a global health crisis framework by employing qualitative research methods, including interviews, observations, and literature analysis. The principal findings highlight that compliance with health protocols as a manifestation of governmental obedience does not mean abandoning the faith but increasing it. This observation points towards the emergence of post-secular religiosity, wherein communities do not relinquish their beliefs in favour of scientific knowledge. Ultimately, this study offers crucial insights into the spiritual resilience exhibited by Muslim communities when confronted with a public health crisis.